Yan-Hou-Qing formula attenuates ammonia-induced acute pharyngitis in rats via inhibition of NF-κB and COX-2 - Min Xu; Tian-Yong Hu; Dong-Cai Li; Li Ma; Hua Zhang; Jun-Ting Fan; Xiao-Mei Fan; Xian-Hai Zeng; Shu-Qi Qiu; Zhi-Qiang Liu; Bao-Hui Cheng (BMC, 2020)
Abstract Background Yan Hou Qing (YHQ) is a Chinese medicinal formula designed to alleviate sore throat symptoms, but underlying mechanism of YHQ treatment for pharyngitis is poorly defined up to now. Methods In this study, the modulation of YHQ on pharyngitis is investigated in ammonia-induced acute pharyngitis rat models. After treatment with YHQ or dexamethasone respectively for five consecutive days, all rats were sacrificed for biomolecular and histopathologic study. Protein expressions of MAPKs, NF-κB, COX-2 and 5-LOX in pharyngitis tissue were evaluated by western blot analysis and the levels of TNF-α, IL-6, prostaglandin (PG) E2, leukotrienes (LT)-B4 and LT-D4 in pharyngeal tissue were measured via ELISA assay. Evans blue (EB) dye exudation test was performed parallelly to assess the integrity of pharyngeal tissue. Results Compared with normal control group, EB dye exudation, and inflammatory cytokines in the model group were significantly increased, and the pharynx tissue was obviously infiltrated by inflammatory cells. YHQ treatment improved the inflammatory infiltrate in pharyngeal tissue, and reduced EB dye exudation in AP rat models. The up-regulated TNF-α and IL-6 in pharyngeal tissue of AP were significantly reduced by YHQ through inhibition of phosphorylation of p38, Erk and NF-κB. YHQ treatment also reversed the increased level of PGE2 through down-regulation of COX-2. Conclusions YHQ formula attenuated the pharyngitis related symptoms via suppression of COX-2 and phosphorylation of p38, Erk and NF-κB (p65).